2015
DOI: 10.1371/journal.pone.0118610
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of BDNF and IGF-1 in Abstinent Cocaine Users with High Prevalence of Substance Use Disorders: Relationship to Psychiatric Comorbidity

Abstract: Recent studies have identified biomarkers related to the severity and pathogenesis of cocaine addiction and common comorbid psychiatric disorders. Monitoring these plasma mediators may improve the stratification of cocaine users seeking treatment. Because the neurotrophic factors are involved in neural plasticity, neurogenesis and neuronal survival, we have determined plasma concentrations of brain-derived neurotrophic factor (BDNF), insulin-like growth factor 1 (IGF-1) and IGF-1 binding protein 3 (IGFBP-3) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Although cocaine has been described to produce a pro-inflammatory state, the decrease in the levels of IL-17α, MIP-1α and TGFα can be interpreted as a compensatory effect that reduces the cocaine-induced inflammatory tone along the period of abstinence in comparison with control subjects. A similar phenomenon has been described for certain growth factor in our outpatient cohort of cocaine patients ( Pedraz et al, 2015 ). However, none of the proteins that were analyzed in the present study were associated with CUD severity, unlike our previously described findings with IL-1β, fractalkine or SDF-1 as severity-sensitive factors ( Araos et al, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although cocaine has been described to produce a pro-inflammatory state, the decrease in the levels of IL-17α, MIP-1α and TGFα can be interpreted as a compensatory effect that reduces the cocaine-induced inflammatory tone along the period of abstinence in comparison with control subjects. A similar phenomenon has been described for certain growth factor in our outpatient cohort of cocaine patients ( Pedraz et al, 2015 ). However, none of the proteins that were analyzed in the present study were associated with CUD severity, unlike our previously described findings with IL-1β, fractalkine or SDF-1 as severity-sensitive factors ( Araos et al, 2015 ).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we attempted to establish potential biomarkers of cocaine consumption and/or comorbid mental disorders by identifying certain, cytokines, chemokines and growth factors in the plasma of patients with these disorders. Previous studies ( Araos et al, 2015 ; Pedraz et al, 2015 ) have revealed that the circulatory/immune system-related signal or growth factors are associated with CUD. The present results extend these observations and indicate that IL-17α, MIP-1α and TGFα are altered in subjects diagnosed with CUD during abstinence, although there was no association with the cocaine symptom severity, and that TGFα levels are also influenced by the presence of dual diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, our research group has found that some of these chemokines -specifically, CCL2, CCL11, CX3CL1, and CXCL12 -are related with depressive symptoms in patients with cocaine [24][25][26] and alcohol 27 use disorders. Following those findings, this study has two main aims: Firstly, the relationship between depression and circulating plasma concentrations of CCL2, CCL11, CX3CL1, and CXCL12 will be tested.…”
Section: Aims Of the Studymentioning
confidence: 92%
“…Link to psoriasis Link to anxiety disorder BDNF (brain-derived neurotrophic factor) responsible for growth and homeostasis of brain neurons Lowered in patients with psoriasis, depression (21), chronic stress (22) Lowered in patients with anxiety disorders (23)(24)(25)(26) CCL2 (chemokine (C-C motif) ligand 2) activates chemotaxis in monocytes and basophils Significant increase in serum of patients with psoriasis (27,28) Increased in patients with anxiety disorder (29) GH1 (growth hormone) required for control of body height Increased in patients with skin diseases, including psoriasis (30) Increased in patients with stress and anxiety disorder (31) CRH (corticotropin-releasing hormone) is synthesized in response to stress and stimulates release of adrenocorticotropin Significant increase in serum of patients with psoriasis (32) Increased in patients with anxiety disorder (31,33,34) LEP (leptin) is secreted by adipocytes, regulates fat and energy metabolism, as well as some endocrine functions and an inflammatory/ immune response Increased in patients with psoriasis (35)(36)(37)(38)(39)(40)(41)(42) Increased in patients with anxiety disorder (43) TNF (tumor necrosis factor), a multifunctional proinflammatory cytokine, is involved in the regulation of a variety of cellular and physiological processes…”
Section: Gene Descriptionmentioning
confidence: 99%